2020
DOI: 10.1073/pnas.1917914117
|View full text |Cite
|
Sign up to set email alerts
|

The α-synuclein hereditary mutation E46K unlocks a more stable, pathogenic fibril structure

Abstract: Aggregation of α-synuclein is a defining molecular feature of Parkinson’s disease, Lewy body dementia, and multiple systems atrophy. Hereditary mutations in α-synuclein are linked to both Parkinson’s disease and Lewy body dementia; in particular, patients bearing the E46K disease mutation manifest a clinical picture of parkinsonism and Lewy body dementia, and E46K creates more pathogenic fibrils in vitro. Understanding the effect of these hereditary mutations on α-synuclein fibril structure is fundamental to α… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 56 publications
8
121
0
Order By: Relevance
“…Furthermore, a recent study on brainderived α-syn fibril showed that in vivo cofactors can participate into α-syn fibril structure and introduce more polymorphs 36 . Recently, several fibril structures formed by inherited α-syn mutants have bee reported including Ac-A53T 37 , H50Q 24 , and E46K 23,38 . The Ac-A53T and H50Q fibrils exhibit similar morphology, and α-syn monomer in these structures folds similarly to that in the Ac-WT fibril ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study on brainderived α-syn fibril showed that in vivo cofactors can participate into α-syn fibril structure and introduce more polymorphs 36 . Recently, several fibril structures formed by inherited α-syn mutants have bee reported including Ac-A53T 37 , H50Q 24 , and E46K 23,38 . The Ac-A53T and H50Q fibrils exhibit similar morphology, and α-syn monomer in these structures folds similarly to that in the Ac-WT fibril ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many approaches describe structures gained via recombinant means under in vitro conditions [2][3][4][5]7,9,10 . Others have employed the use of lipids during in vitro experiments, since this is critical to αS function in situ 6,[11][12][13][14][15][16][17] . More recent studies are emerging in which aggregates of αS from specific neurodegenerative diseases and key regions of the brain are isolated in small quantities 8,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The number and location of β-strands within this region, however, varies between fibril polymorphs generated under different solution conditions, with the ionic strength, the presence of polyanions or the pH of the solution as main factors for fibril structure variability. These observations, therefore, already highlight the relevance of electrostatic interactions in the intramolecular and intermolecular forces that define the overall structure in the different amyloid polymorphs [119,124,125]. Two regions within the amyloid core have been suggested to be important for stabilizing the amyloid structure [123], concretely 71-82 region, which was also found to be essential for the initiation of the aggregation process [126], and 45-57 region, where most of the pathological point mutations are located.…”
Section: Fibrillar Polymorphsmentioning
confidence: 85%
“…The presence of such mutations were suggested to affect severely the protofilament arrangement and then the stability of mature fibrils, which was correlated with the potential increase in the fraction of toxic oligomeric species within the cells [125]. The E46K pathological mutation, however, was later reported to adopt a significantly different amyloid fold as compared to the amyloid structure adopted by the WT protein at similar conditions [124,125]. The acquisition of this alternative fibril kernel conformation by the E46K mutation results in a significantly higher propensity to seed the formation of new fibrils as compared to the WT fibrils [124,125], which could influence the speed of αS pathology spreading.…”
Section: Possible Roles Of α-Synuclein Species In Cell-to-cell Propagmentioning
confidence: 99%
See 1 more Smart Citation